2017
DOI: 10.1038/onc.2017.46
|View full text |Cite
|
Sign up to set email alerts
|

Compromised BRCA1–PALB2 interaction is associated with breast cancer risk

Abstract: The major breast cancer suppressor proteins BRCA1 and BRCA2 play essential roles in homologous recombination (HR)-mediated DNA repair, which is thought to be critical for tumor suppression. The two BRCA proteins are linked by a third tumor suppressor, PALB2, in the HR pathway. While truncating mutations in these genes are generally pathogenic, interpretations of missense variants remains a challenge. To date, patient-derived missense variants that disrupt PALB2 binding have been identified in BRCA1 and BRCA2; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(121 citation statements)
references
References 57 publications
7
108
2
4
Order By: Relevance
“…The strongest evidence to date of a bi‐allelic inactivation requirement for PALB2 is from analysis of a single PALB2 tumour where exome sequencing identified a somatic nonsense mutation, presumably in the wild‐type allele. This tumour also showed a very high LST score and a mutation signature 3, both consistent with loss of homologous DNA repair capacity . However, none of the other studies performed full exon sequencing of PALB2 .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The strongest evidence to date of a bi‐allelic inactivation requirement for PALB2 is from analysis of a single PALB2 tumour where exome sequencing identified a somatic nonsense mutation, presumably in the wild‐type allele. This tumour also showed a very high LST score and a mutation signature 3, both consistent with loss of homologous DNA repair capacity . However, none of the other studies performed full exon sequencing of PALB2 .…”
Section: Discussionmentioning
confidence: 77%
“…Mutation signatures were also assessed based on 110 SNVs identified in PALB2 germline mutation tumours (43 SNVs among the HET group and 67 among the NULL group) and 225 SNVs among the 35 sporadic breast tumours. The PALB2 tumours, but not the sporadic tumours, showed a prominent somatic mutation signature 3 (36.5% versus 0%) consistent with defective homologous recombination [13,28,38] (supplementary material, Figure S2). Because of the small number of mutations, it was not possible to derive reliable signatures for the PALB2 heterozygous and PALB2-null tumours separately.…”
Section: Homologous Recombination Deficiency In Palb2 Tumoursmentioning
confidence: 92%
“…BRCA1 promotes the displacement of 53BP1 from chromatin surrounding DSBs and consequently activates DNA end resection (Chapman et al, 2012; Densham et al, 2016). After DNA end resection, BRCA1 directly interacts with and recruits PALB2 to DSB sites, where BRCA2-RAD51 form s a com plex with PALB2, and mutations that block the BRCA1-PALB2 interaction have been shown to reduce the efficiency of RAD51 foci formation and HR (Anantha et al, 2017; Foo et al, 2017; Sy et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…PALB2 is a binding partner of BRCA1 and also an essential protein for the normal function of BRCA2 during repair of DNA double stranded breaks . A recent study has identified that defective PALB2‐BRCA1 interaction is associated with increased BC risk . California Teachers Study, a nested case–control study (1,353 cases and 1,384 controls), identified several single nucleotide polymorphisms (SNPs) in apoptosis initiator CASP8 that were associated with BC risk, while SNP rs2293554 of CASP8 was specifically associated with HER2 + BC (OR = 1.98, 95% CI 1.34–2.92) .…”
Section: Determinants Of Bc Risk: Considerations For Bc Prevention Anmentioning
confidence: 99%
“…22 A recent study has identified that defective PALB2-BRCA1 interaction is associated with increased BC risk. 23 California Teachers Study, a nested case-control study (1,353 cases and 1,384 controls), identified several single nucleotide polymorphisms (SNPs) in apoptosis initiator CASP8 that were associated with BC risk, while SNP rs2293554 of CASP8 was specifically associated with HER2 1 BC (OR 5 1.98, 95% CI 1.34-2.92). 24 The combined loss of TP53 and PTEN leads to accelerated development of BC that is dependent on eukaryotic elongation factor-2 kinase (eEF2K).…”
Section: Determinants Of Bc Risk: Considerations For Bc Prevention Anmentioning
confidence: 99%